Segurança institucional e violência: o que revelam os dados na Universidade Federal da Paraíba - UFPB - Vilar, Peterson Rodrigues Macêdo (2022)
The current work aims at the forms of violence that hapen at the Federal University of Paraíba, whether violence committed by students, teachers, technicians, professors or institutional violence. The research is carried out on the theoretical concept of violence, through the evaluation of some indicators of national violence and indicators of the state of Paraíba. General guidelines and public policies to prevent violence are also investigated, both within the scope of the United Nations on Drugs and Crime 2021-2025 (UNODC) and the National Plan for Public Security and Social Defense 2021-2030 (NPS). The concepts of data and information are analyzed based on the DIKW pyramid. From the point of view of the Federal University of Paraíba (FUPB), we analyzed its Institutional Security Policy, its actions and competencies. For this, a survey was carried out of the bodies responsible for this security, the Institutional Security Superintendence (SSI), the General Ombudsman of the Federal University of Paraíba and the Permanent Commission for Disciplinary Administrative Process and Accountability (CPRADR). The reports produced by these sectors are examined in order to understand what are the violent acts that occur in the institution, where they occur and how they are treated. Finally, it was observed that the FUPB does not have a formal document on its internal security policy and that data collection in the various sectors are not shared with each other, so that there is no institutional integration on the total security problems in the institution.